Maize Endosperm Development: Tissues, Cells, Molecular Regulation and Grain Quality Improvement - Wu, Hao; Becraft, Philip W.; Dannenhoffer, Joanne M. (Frontiers in Plant Science, 2022)
Maize endosperm plays important roles in human diet, animal feed and industrial applications. Knowing the mechanisms that regulate maize endosperm development could facilitate the improvement of grain quality. This review provides a detailed account of maize endosperm development at the cellular and histological levels. It features the stages of early development as well as developmental patterns of the various individual tissues and cell types. It then covers molecular genetics, gene expression networks, and current understanding of key regulators as they affect the development of each tissue. The article then briefly considers key changes that have occurred in endosperm development during maize domestication. Finally, it considers prospects for how knowledge of the regulation of endosperm development could be utilized to enhance maize grain quality to improve agronomic performance, nutrition and economic value.